Constraints Faced by Officials of Livestock based Self Help Group Promoting Institutes (SHGPIs) in Punjab, India - Chadda, Akshita; Y.S. Jadoun; Singh, Jaswinder; Singh, S.K. Kansal (Journal of Agricultural Extension Management, 2022)
Even though livestock based women Self Help Groups (SHGs) act as a means to mobilize poor women and to make them self reliant, it has been observed that various constraints hinder the effective and efficient functioning of these groups. A study was conducted in Ludhiana district of Punjab to know the constraints faced by concerned officials of livestock based Self Help Group Promoting Institutes (SHGPIs) viz., a dairy cooperative, Government and Non-Government Organization (NGO). Findings revealed that among dairy cooperative officials, inadequate staff at the field level, poor attitude of the members and lack of participation at member's level were the major constraints in order of severity. Inadequate staff for regular follow up of SHGs, lack of advertisement at the farmer level and utilization of budget for other activities rather than for livestock, were constraints faced by the officials from SHGs promoted by government organizations. Lack of required skill-based training to the members, lack of public participation, poor governance and networking and absence of cohesive and strategic planning were the major constraints faced by the NGO officials. For the proficient functioning of livestock based SHGs in a sustainable manner, there is a need to eliminate these constraints on a priority basis.